Strengthening Pancasila-Based Digital Ethics Among Gen Z: A Community Service Program in SMA Negeri 34 Jakarta - Hartanto; Suprayitno, Dede; Wardani, Ayu; Hayati, Kumala (Warta Pengabdian Andalas, 2026)
As Indonesia’s foundational ideology, Pancasila faces considerable challenges in the digital age, particularly among Generation Z, who, as digital natives, often struggle to embody its values in online interactions. This study examines both the comprehension and application of Pancasila values among students at SMA Negeri 34 Jakarta, while evaluating the effectiveness of a community service program aimed at reinforcing digital ethics through a Pancasila-based framework. Namely by using the quasi-experimental one group pre-post design method. The program adopted an interactive pedagogical approach, integrating real-world case analyses and digital challenges to reconceptualize Pancasila from an abstract normative ideal into a practical moral compass. Empirical findings reveal that prior to the intervention, students demonstrated a limited grasp of Pancasila’s principles, reflected in an average pre-test score of 5.1 out of 10. Following participation in the program, the average post-test score rose significantly to 8.9 out of 10, representing a 74.5% improvement. This substantial increase highlights the efficacy of contextual and practice-oriented methodologies in bridging the gap between ideological principles and behavioral practices. The findings affirm the enduring relevance of Pancasila as a moral framework for Generation Z within digital environments, while offering a replicable model for the integration of Pancasila-based character education in secondary schools across Indonesia. However, this study has causal limitations, as it only measured student outcomes in urban areas and public schools. Different outcomes may be found in rural or religious schools.